Sablefish (Anoplopoma fimbria) parentage analyses in aquaculture. (19th December 2021) - Rubi, Tricia L.; McPherson, Alana G.; Mokariasl, Niloufar; Koop, Ben F.; Campbell, Briony; Taylor, John S.
Abstract: Sablefish ( Anoplopoma fimbria ) is a commercially valuable species in Canada with limited aquaculture development. In this study, we partner with Golden Eagle Sablefish in British Columbia (Canada) to assess the role of brood stock selection in hatchery production. Mortality in the hatchery setting is high, especially during the first year of development; thus, interventions that enhance early survival have the potential to dramatically improve productivity. Here, we determined the parentage of offspring produced by a brood stock population of 12 females and 6 males. Focusing on a 2019 hatchery cohort (' Implant 5 2019 '), we sampled offspring at 9 months ( N = 70) and 12 months of age ( N = 124). We observed considerable family‐level variation in productivity; out of 30 crosses, 5 pairs produced 69% of the progeny. At the individual level, 5 of the 12 brood stock females produced 90% of the offspring surveyed, and 3 of the 6 males sired 93% of the offspring. These data provide strong support for the hypothesis that sablefish survival in the hatchery setting can be improved through selective breeding.